Productive and Biological Characteristics of Growing Sheep with Different Genotypes (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: sheep; breeds; raising; breeding; selection; dairy productivity; chemical composition of milk; hematology; correlation